AB0443 Infusion reactions to rituximab in systemic lupus erythematosus: a retrospective analysis. (15th June 2017) - Hennessey, A; Lukawska, J; Cambridge, G; Isenberg, D; Leandro, M
Abstract : Background: B-cell depletion with Rituximab (RTX) has been used since since 2000 in the treatment of Systemic Lupus Erythematosus (SLE). An issue with the use of RTX is the attrition rate due reactions during of following infusions. This can prevent re-treatment with RTX in patients with a good initial response to RTX and in whom other treatments had failed, this is especially important in SLE patients with limited biologic options. Objectives: To identify the rates and patient characteristics of infusion reactions to RTX in patients with SLE. Methods: A retrospective analysis of the SLE patient cohort receiving RTX at University College London Hospitals via examination of patient records was used to determine if there was a clinically significant reaction (from clinic letters or discharge summary) for each RTX infusion. One cycle of RTX refers to 2 infusions given 2 weeks apart. A descriptive analysis of the reaction was recorded as was the decision making surrounding the infusions. Results: Records from 151 RTX-treated patients were reviewed with 13 excluded due to missing data. 138 remaining patients (130 females and 8 males, mean age (1st infusion) =33 years; range: 16–73) received a total of 478 individual RTX infusions (between 1–9 cycles). Prior to 2007, standard of care was to receive Cyclophosphamide (CYC) with each cycle. The total rate of infusion reactions was 5.85% (23 patients had 28 reactions). Of these 4 (50%) were males, 19 females (14.6%; p =0.009, Chi square). Average number of cycles in those without, compared to with a reaction was 1.61 vs 1.64. With 1st dose, 7 patients (25%) had reactions, 19 with 2nd (67.9%). 3 patients were retreated (1 twice); 2/3 had further reactions and the 3rd two further cycles without issues. Most were not retreated. Reactions ranged from mild to severe (Table 1 ). A total of 24 RTX reactions were categorized into: Immediate- unlikely immune mediated 4; likely cytokine release 7; IgE mediated 5; and bone pain reactions 2. Delayed- early (24–48hours) 1; and late (>48hours) 5; by a Clinical Allergist. 4 reactions were excluded from this analysis; 1 death as likely CYC induced (but occurred within 24 hours of RTX) and 3 due to lack of data. Conclusions: The number of previous cycles was similar in patients who reacted versus those who did not. Patients were most likely to experience a clinically significant reaction with the second infusion. Males had higher incidence of reactions. Most (19%) were immediate and the majority (79%) of immediate and delayed reactions occurred during 1st (10) and 2nd (9) cycles. The total rate of infusion reactions in this cohort was lower than previously reported however this is likely contributed to by the limitations of a retrospective review. However 64% of reactions (11/17) in this cohort were significant, necessitating cessation of infusion or hospital admission. Disclosure of Interest: A. Hennessey: None declared, J. Lukawska: None declared, G. Cambridge: None declared, D. Isenberg: None declared, M. Leandro Consultant for: Roche UK and Roche Basel and Genentech